2016
DOI: 10.18553/jmcp.2016.22.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Glycemic Control of a Pharmacist-Led Medication Management Program in Patients with Type 2 Diabetes

Abstract: A pharmacist-led diabetes MMP, combined with a diabetes drug copay waiver, was effective in significantly reducing A1c over a 2-year period for type 2 diabetic patients in this regional health plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…One study used a case-control study design and had a moderate risk of bias [ 86 ]. 14 were pre-post studies; one had a high risk of bias [ 87 ], 11 had medium risk of bias [ 88 – 98 ], and two had low risk of bias [ 99 , 100 ]. Six studies were record/chart reviews: two were assessed to have low risk of bias [ 101 , 102 ] and four had medium risk of bias [ 103 106 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study used a case-control study design and had a moderate risk of bias [ 86 ]. 14 were pre-post studies; one had a high risk of bias [ 87 ], 11 had medium risk of bias [ 88 – 98 ], and two had low risk of bias [ 99 , 100 ]. Six studies were record/chart reviews: two were assessed to have low risk of bias [ 101 , 102 ] and four had medium risk of bias [ 103 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such studies tended to consider context within the narrative of diabetes control in their region. 32 studies described the national context in which the study took place [ 25 , 27 , 31 , 33 , 42 , 43 , 48 , 50 , 51 , 54 , 59 62 , 66 , 67 , 74 , 80 – 82 , 85 , 86 , 91 , 92 , 96 , 98 , 100 , 104 , 111 , 112 , 115 , 116 ]. This typically involved descriptive statistics to indicate the magnitude and urgency of diabetes as a national challenge, highlighting incidence or prevalence rates and cost burden.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown positive associations between pharmacist-led management program and the clinical outcomes considered in this study. 13 16 A meta-analysis of 15 randomized controlled trials also noted significant improvements in cardiovascular risk factors related to pharmacist-managed care. 17 However, there are clear differences between these previous studies and the current study including differences in settings (eg, Veterans Affairs and community health center vs integrated health system), study design (eg, randomized clinical trial vs observational study), lower individual study sample sizes, and the differences in the design and maturity of the disease management programs.…”
Section: Discussionmentioning
confidence: 99%